LEGAL PROTECTION FOR VICTIMS OF FAIR TRIAL RIGHTS AS A FORM OF HUMAN RIGHTS PROTECTION IN THE INDONESIAN JUSTICE SYSTEM - Aji Febrian Nugroho (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
In the legal protection of the right of Fair Trial victims in the Indonesian judicial system, the government should refer to and protect the Human Rights that exist in every individual human being even though the person who violates the “Fair Trial right” is a perpetrator of the crime. This study aims to examine the extent of the form of legal protection for victims of Fair Trial rights as a form of human rights protection in the Indonesian Judicial System because cases of violations of Fair Trial rights are often found in various existing cases. The “Fair Trial Rights” violated are the basic value of the criminal justice process covering at least three important components: human dignity, truth, and justice in the process. The first basic value, namely the protection of human dignity refers to the condition that all law enforcement officers at all stages of the judiciary must apply consistently and support the protection of the human dignity of the parties, both suspects, defendants, convicts, victims, and witnesses, the second value is the value of truth, this value requires that law enforcement “must ensure the application of normative provisions before imposing accusations, indictment, or punishing a person”, while the third value is fairness or the value of justice in criminal justice proceedings, which requires that law enforcement must work hard to treat the parties by respecting their rights protected by law and applying the limits of their authority.